A Feasibility Study on Organique Cosmetics Corporation - Balois, Stephanie C.; Ching, Dioselle S.; Lim, Loubert Peter A. (Diliman, Quezon City College of Engineering, 2003)
Organique Cosmetics Corporation manufactures the Organique Cosmetics Line. The company aims to provide users with high quality, Filipino-made make-up that are entirely made from organic raw materials. The manufacturing procedures are environment-friendly and the products are never tested on animals. To determine the success of the project, a project feasibility study was done to thoroughly and systematically analyze all the factors that affect the possibility of success of the product. The feasibility study is a synthesis of the studies dealing with marketing, technical, financial, and social profitability aspects of the project. In the marketing study, the name Organique was decided to denote that the raw materials are organic and it has positive representation. It was also determined that there is a demand for organic cosmetics and the company can have forecasted sales of Php 192,362,513.04 from its market share. There would be six cosmetic products and one packaging vessel. These are the foundation, face powder, eyeshadow, blush, lipstick, make-up remover and the multi-case. The foundation is available in six colors named after the colors of the soils of the biomes. These are the tundra, oasis, coastal, desert, savannah and taiga. The face powder colors are named after nuts of the same shade which are the pistachio, cashew, pecan, hazelnut, coconut, and chestnut. The eyeshadows were named after flowers aside for the cocoa shade. These are the magnolia, larkspur, honeysuckle, rose and lilac. There are three blush shades named after barks of tree which are the oak, dogwood and birch. There are also three shades of lipstick named after natural phenomenon: earthquake, eruption and sandstorm. The two make-up removers are for the eyes called dew and for the face called rain. The multi-case is a cosmetic palette containing one eyeshadow, blush and lipstick. It allows users to customize the colors since the multi-case is magnetized and the products have metallic bases. To market the products, the company would advertise in Preview, Seventeen and Cosmopolitan magazines would have feature stories in the Philippine Star and would join annual bridal fairs. The product would be launched at the Manila Diamond Hotel. In the technical study, it was determined that the company would employ a one-worker-multiple-machine strategy because of its high variety and low volume nature and to ensure its quality. The suppliers of the raw materials, packaging materials, production equipment, office supplies and equipment were determined. The capacity of the plant was also established to have three lines: the liquid line manufacturing the foundation, make-up remover and some of the lipstick, the lipstick line manufacturing only lipsticks and the powder line manufacturing the eyeshadow, blush and face powder, the multi-case would be outsourced. The statistical quality control will also be implemented using acceptance sampling with the Lot Tolerance Percent Defective Plan to ensure high quality. The facility layout was also planned and was determined to be located at Pioneer St. in Mandaluyong City. The organization would be in the form of a private corporation and would have 21 employees. In the financial study, the total project?s cost was calculated. To finance the study, it was determined that the company would loan 50% of its required start-up cost of Php 12,358,756.60 at an interest of 21% per annum to be paid equally in five years. The remaining 50% would be financed by selling equity shares at a par value of Php 1.00. The forecasted pro forma financial statements were generated specifically the cash flows statement, income statement and balance sheet. The company?s financial standing was evaluated by evaluating the significant financial ratios and the investment?s net present value, internal rate of return was greater than the set minimum attractive rate of return of 21% and the project?s payback period is less than one year. In the social profitability analysis, the primary and secondary benefits to the community and government were evaluated against its costs. By computing the net present value, internal rate of return and benefit-cost ratio, the company was found to be socially profitable. The market, technical, financial and social feasibility studies were then evaluated from the point of view of its optimality, practicality, potential and growth. Since the studies pertaining to the product?s market, technical, financial and social profitability aspects were all found to be feasible, it is concluded that the over-all project is feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Organique Cosmetics Corporation; Herbal cosmetics; Beauty, Personal; Women--Health and hygiene; Participatory monitoring and evaluation (Project management)